2023
DOI: 10.1002/fsn3.3407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sesame (Sesamum indicum L.) and bioactive compounds (sesamin and sesamolin) on inflammation and atherosclerosis: A review

Elham Hadipour,
Seyed Ahmad Emami,
Niloufar Tayarani‐Najaran
et al.

Abstract: Inflammation, oxidative stress, obesity, infection, hyperlipidemia, hypertension, and diabetes are the main causes of atherosclerosis, which in the long term lead to hardening of the arteries. In the current study, we reviewed recent findings of the mechanism of sesame and its active compounds of sesamin and sesamolin regulates on atherosclerosis. Sesame can decrease the lipid peroxidation and affect the enzymes, which control the balance of oxidative status in the body. Besides modulating the inflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 218 publications
(294 reference statements)
0
3
0
Order By: Relevance
“…Administration of 300 mg/kg CVE has been shown to effectively mitigate microglial activation and suppress the phosphorylation of JNK, ERK, and p38 and the expression of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α was significantly reduced, leading to an amelioration of the inflammatory response and neuronal damage ( WANG et al, 2022a ). 4-Hydroxysesamin , a lignan constituent of tetrahydrofuran , is obtained from Chinese herbs including Rhizoma hydroxysesamin , Watkins , and camphor, and has been found to possess anti-stroke properties ( HADIPOUR et al, 2023 ). Research has demonstrated that 4-hydroxysesamin exerts its protective effects on cerebral ischemic tissue by down-regulating the expression of COX-2 and IL-6 through the inhibition of the p38MAPK signaling pathway ( ZHANG et al, 2021 ).…”
Section: The Mechanism Of Tcmhs Intervention In Microglia and Its Rel...mentioning
confidence: 99%
“…Administration of 300 mg/kg CVE has been shown to effectively mitigate microglial activation and suppress the phosphorylation of JNK, ERK, and p38 and the expression of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α was significantly reduced, leading to an amelioration of the inflammatory response and neuronal damage ( WANG et al, 2022a ). 4-Hydroxysesamin , a lignan constituent of tetrahydrofuran , is obtained from Chinese herbs including Rhizoma hydroxysesamin , Watkins , and camphor, and has been found to possess anti-stroke properties ( HADIPOUR et al, 2023 ). Research has demonstrated that 4-hydroxysesamin exerts its protective effects on cerebral ischemic tissue by down-regulating the expression of COX-2 and IL-6 through the inhibition of the p38MAPK signaling pathway ( ZHANG et al, 2021 ).…”
Section: The Mechanism Of Tcmhs Intervention In Microglia and Its Rel...mentioning
confidence: 99%
“…Sesamin is the most prominent lignan compound found in sesame seeds, one of the two highest sources of lignans (the other being flax) in the human diet. Sesamin is catered to be a nutritional supplement that is believed to possess various properties such as anti-inflammatory, pro-apoptotic, pro-angiogenic, antimetastatic, antiproliferative, and ant-oxidant effects, as well as pro-antiphagocytic activities (if touting its health properties) or possibly being an estrogen receptor modulator and fat burner (if targeting athletes or persons wishing to lose weight) [56,60]. Sesamin has several processes, which, when considered comprehensively, may be succinctly described as a modulator of fatty acid metabolism.…”
Section: Sesaminmentioning
confidence: 99%
“…Sesame seeds (Sesamum indicum L.) contain a multitude of phenolic compounds, which exhibit beneficial effects on human health. Phenolic components, known for their antioxidant, anti-inflammatory and hypolipidemic activities, and, specifically, sesame lignans like sesamin and sesamolin have attracted large interest regarding their nutritional benefits for humans in conditions such as atherosclerosis, hypertension, hyperlipidemia, obesity, diabetes, osteoporosis, arthritis and Alzheimer's disease [1][2][3][4][5][6][7][8]. A number of studies with sesame oil have reported a reduction in oxidative stress and an increase in vitamin E levels [9,10].…”
Section: Introductionmentioning
confidence: 99%